Talleres didácticos para reducir las consecuencias socio afectivas que ocasiona el maltrato infantil en niños y niñas de educación inicial del CIBV Mulalillo de la parroquia Mulalillo, cantón Salcedo, provincia de Cotopaxi, en el año 2014 - 2015 - Sandoval Morales, Adriana Maricela (2015)
This workis based on the proposal “Educational workshops developed with parents and teachers in order to reduce the socio-affective consequences produced on children abuse at Mulalillo CIBV. It is critical for normal development and school performance. The goal research is to determine how the training workshop on well improvement at the Children Center before mentioned. This is based on a non-experimental, quantitative and qualitative study. The sample of 36 parents / mothers, representing 36 children. Research techniques and procedures such as surveys of parents and teachers of the 36 children at the Children´s Center were applied and the fundamentals of the Code for Children and Adolescents lack guidance on the appropriate treatment to be provide to infants who were observed. In addition, the awareness of Local and Institutional Authorities on the treatment those parents should provide their children. This work is based on the proposal to develop educational workshops for parents and teachers with the aim of reducing the socio-emotional consequences on Children´s in-appropriate treatment.